THE MANAGEMENT MODEL FOR SMALL AND MEDIUM-SIZED MINING COMPANIES IN THE EPIDEMIC ERA: A CASE STUDY OF COMPANY W - Luo, Piyun; Yang , Shuchen (Journal of Buddhist Education and Research (JBER), 2023)
China is rich in mineral resources, but its per capita possession is small. Therefore, most of the mine resources depend on imports. However, due to the impact of the COVID-19, ore imports have been hindered, and managers engaged in small and medium-sized mining enterprises still have a low level of education, lacking professional system management knowledge and managing companies based on their experience. Therefore, tis paper aimed to investigate the operation of Company W, a Chinese mining company, and analyze its comprehensive management to provide a new reference for the management analysis for similar small and medium-sized companies. Data were obtained through in-depth interviews following Maslow’s hierarchy of needs theory and the Employee Boston Model, and the informants were selected through stratified sampling. Data were analyzed based on the lean management theory and the six sigma management theory. According to the result, Company W the enterprise’s staff enthusiasm is poor, the management level is chaotic, shareholders communication mode is single. In view of the above problems, the new management mode needs to improve the enthusiasm of employees, rebuild the management structure, increase communication channels and so on. The study of this paper provides a new reference for the similar management analysis of small and medium-sized enterprises and provides new ideas for the management of small and medium-sized mining enterprises.